2011
DOI: 10.1051/0004-6361/201016345
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the origin of magnetic fields in massive stars: a survey of O-type stars in clusters and in the field

Abstract: Context. Although the effects of magnetic fields in massive stars have been found to be substantial by recent models and observations, the magnetic fields of only a small number of massive O-type stars have so far been investigated. Additional observations are of the utmost importance to constraining the conditions that are conducive to magnetic fields and to determine the first trends about their occurrence rate and field strength distribution. Aims. To investigate statistically whether magnetic fields in mas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
100
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 78 publications
(112 citation statements)
references
References 44 publications
(69 reference statements)
11
100
1
Order By: Relevance
“…The feasibility of longitudinal magnetic field measurements in massive stars using low-resolution spectropolarimetric observations was demonstrated by previous studies of O-and B-type stars (e.g., Hubrig et al 2006Hubrig et al , 2009Hubrig et al , 2008Hubrig et al , 2011cHubrig et al , 2013Hubrig et al , 2015b. A number of discrepancies in the published measurement accuracies using FORS 1 data were reported by Bagnulo et al (2012), who used the ESO FORS 1 pipeline to reduce the FORS 1 archive.…”
Section: Magnetic Field Measurementsmentioning
confidence: 97%
See 1 more Smart Citation
“…The feasibility of longitudinal magnetic field measurements in massive stars using low-resolution spectropolarimetric observations was demonstrated by previous studies of O-and B-type stars (e.g., Hubrig et al 2006Hubrig et al , 2009Hubrig et al , 2008Hubrig et al , 2011cHubrig et al , 2013Hubrig et al , 2015b. A number of discrepancies in the published measurement accuracies using FORS 1 data were reported by Bagnulo et al (2012), who used the ESO FORS 1 pipeline to reduce the FORS 1 archive.…”
Section: Magnetic Field Measurementsmentioning
confidence: 97%
“…Recent detections of strong magnetic fields in very fast rotating early B-type stars indicate that the spindown timescale via magnetic braking can be much longer than the estimated age of these targets (e.g., Rivinius et al 2013). Furthermore, current studies of their kinematical status identified a number of magnetic O and Of?p stars as candidate runaway stars (e.g., Hubrig et al 2011c). Increasing the known number of magnetic objects with extreme rotation, which are probably products of a past binary interaction, is important to understanding the magnetic field origin in massive stars.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, new Of?p stars were identified in the Galaxy, with very similar characteristics (Walborn et al 2010): NGC 1624-2 (period of 158 d, Wade et al 2012b) and CPD−28 • 2561 (Hubrig et al 2011(Hubrig et al , 2013period of 73 d, Wade et al 2015). It must be stressed that, while about ten O stars are now known to be magnetic, the only actual class of magnetic massive stars is the Of?p category.…”
Section: Introductionmentioning
confidence: 94%
“…In this context, the recurrence timescale is the rotational period, and long rotation periods may then be explained by magnetic braking over the lifetime of the star (ud-Doula et al 2009). This implied that all Of?p stars are strongly magnetic, and HD 108 and HD 148937 were indeed soon found to be so (Hubrig et al 2008(Hubrig et al , 2011(Hubrig et al , 2013Martins et al 2010;Wade et al 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…For best visibility of the Zeeman features, we overplot the Stokes V spectra of IGR J11215−5952 with the Stokes V spectra of the two well-known magnetic early B-type stars HD 96446 and ξ 1 CMa. Regarding the significance of the magnetic field detections in massive stars at significance levels around 3σ, we note that the two clearly magnetic Of?p stars HD 148937 and CPD −28 • 5104 have been for the first time detected as magnetic in our FORS 2 observations at significance levels of 3.1σ and 3.2σ, respectively (Hubrig et al 2008(Hubrig et al , 2011. The detection of the magnetic field in IGR J11215−5952 at significance levels of 3.2σ and 3.8σ indicates that this target likely possesses a kG magnetic field.…”
Section: Observations and Magnetic Field Measurementsmentioning
confidence: 99%